Turning demographic change into opportunity : HR Strategies for an aging workforce in Germany - Tomášová, Zuzana; Stříteský, Marek; Hořáková, Marie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis investigates how German companies can adapt to the challenges of an ageing workforce. The research combines demographic analysis, a review of international and national frameworks of age-inclusive management, and an empirical survey among employees aged 50+. The findings show that while the overall sentiment toward existing HR practices is mixed, two factors, knowledge management and retirement pathways, play a decisive role in employees’ willingness to remain in employment until and beyond the statutory retirement age. Other factors, such as organizational culture, intergenerational cooperation, and health management, proved less significant. The thesis concludes that focusing on structured knowledge transfer and flexible, transparent retirement schemes offers the greatest potential for German employers to mitigate demographic risks, sustain workforce capacity, and transform ageing into a source of competitive advantage.
Vedoucí práce: Marek Stříteský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses